d d x ( f ( x ) g ( x ) ) = ( g ′ ( x ) ln ( f ( x ) ) + g ( x ) f ′ ( x ) f ( x ) ) f ( x ) g ( x ) {\displaystyle \frac d{dx} (f(x)^{g(x)}) = \Big(g'(x)\ln(f(x)) + \frac {g(x)f'(x)}{f(x)} \Big)f(x)^{g(x)}}
d d x ( f ( x ) g ( x ) ) {\displaystyle \frac d{dx} (f(x)^{g(x)})}
= d d x ( e ln ( f ( x ) g ( x ) ) ) {\displaystyle = \frac d{dx} \big(e^{\ln(f(x)^{g(x)})}\big)}
= d d x ( e g ( x ) ln ( f ( x ) ) ) {\displaystyle = \frac d{dx} \big(e^{g(x)\ln(f(x))}\big)}
Chain rule and e x {\displaystyle e^x} derivative:
= ( g ( x ) ln ( f ( x ) ) ) ′ ( e g ( x ) ln ( f ( x ) ) ) {\displaystyle = (g(x)\ln(f(x)))' \big(e^{g(x)\ln(f(x))}\big)}
Product rule:
= ( g ′ ( x ) ln ( f ( x ) ) + g ( x ) ( ln ( f ( x ) ) ′ ) ( e ln ( f ( x ) ) ) g ( x ) {\displaystyle = (g'(x)\ln(f(x)) + g(x)(\ln(f(x))') \big(e^{\ln(f(x))}\big)^{g(x)}}
ln ( x ) {\displaystyle \ln(x)} derivative and chain rule:
= ( g ′ ( x ) ln ( f ( x ) ) + g ( x ) f ′ ( x ) f ( x ) ) f ( x ) g ( x ) {\displaystyle = \Big(g'(x)\ln(f(x)) + \frac {g(x)f'(x)}{f(x)}\Big) f(x)^{g(x)}}
= ( x ′ ln ( x ) + x ⋅ x ′ x ) x x {\displaystyle = \Big(x' \ln(x) + \frac {x \cdot x'}{x}\Big) x^x}
= ( ln ( x ) + 1 ) ⋅ x x {\displaystyle = (\ln(x) + 1) \cdot x^x}